1997
DOI: 10.1021/bi9711442
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-Sensitive Residues and Pore Site in AQP3 Water Channel

Abstract: Water channel function of all aquaporins (AQPs) but AQP4 can be inhibited by mercurial reagents. Mercurial reagents are believed to bind specifically to cysteine residues and block the aqueous pore of AQPs. Because of the low homology of AQP3 to other AQPs, it is not certain whether the pore structure of AQP3 is similar to that of the others. Determination of mercury-sensitive cysteine residues in AQP3 and comparison with those in other AQPs will help to resolve this question. When AQP3 was expressed in Xenopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 18 publications
3
62
2
Order By: Relevance
“…However, it was not possible to reverse this effect by mercaptoethanol treatment. This is in contrast to the observations of human AQP3 and AQP10, where at 1·mmol·l -1 HgCl2 there is significant inhibition of water transport, which is partially reversed in the presence of mercaptoethanol (Ishibashi et al, 2002;Kuwahara et al, 1997b).…”
Section: Cloning Of Cdna and Amino Acid Sequence Analysiscontrasting
confidence: 99%
“…However, it was not possible to reverse this effect by mercaptoethanol treatment. This is in contrast to the observations of human AQP3 and AQP10, where at 1·mmol·l -1 HgCl2 there is significant inhibition of water transport, which is partially reversed in the presence of mercaptoethanol (Ishibashi et al, 2002;Kuwahara et al, 1997b).…”
Section: Cloning Of Cdna and Amino Acid Sequence Analysiscontrasting
confidence: 99%
“…Mercury affects AQPs by acting on cysteine residues of the water channels. The mercury-sensitive cysteine in AQP3, Cys 11 , is located in the NH 2 -terminal part of the protein (23). Thus, mercury has to penetrate the cell membrane to reach its target, which makes the mercury effect relatively slow.…”
Section: Discussionmentioning
confidence: 99%
“…AQP3 is a relatively weak transporter of water but functions as an efficient glycerol transporter (4). Reflection coefficient measurements (5) and mutagenesis studies (6) suggested that water and glycerol share a common pathway through the AQP3 protein, although inhibition experiments were interpreted as suggesting different pathways (7). Immunocytochemistry in rat showed AQP3 protein expression in basolateral membrane of kidney collecting duct and large airways, as well as in several tissues that are thought not to have an important water-transporting role including urinary bladder, conjunctiva, and epidermis (8)(9)(10)(11).…”
mentioning
confidence: 99%